Growth and physiological state of beech seedlings grown in a nursery in different light conditions - A. Jurásek; J. Leugner; J. Martincová (Journal of Forest Science, 2010)
Seedlings of European beech of two populations (from the 4th and 7th forest altitudinal zone) were grown in a shaded and unshaded plastic greenhouse. The objective was to compare seedling growth and the function of assimilatory organs and to determine their reactions after transfer to different light conditions.Seedlings grown in the unshaded plastic greenhouse (the sun variant) were taller and stronger at the end of the first growing season and had the higher weight and volume of shoots and root systems than seedlings grown in the shade. A higher number of leaves, larger total leaf area and higher dry matter of leaves per 1 plant were determined in seedlings grown in the sun. The average area of one leaf was larger in seedlings grown in the shade. The higher photosynthetic electron transport rate (ETR) determined from the light curves of chlorophyll fluorescence in seedlings grown in the sun was apparently connected with the higher photosynthetic rate and more intensive growth of these seedlings. The transfer of seedlings from full sun to shade resulted only in small changes in chlorophyll fluorescence (Fv/Fm, ETR). On the contrary, the transfer of seedlings from the shaded plastic greenhouse to the sun induced photoinhibition leading to a significant reduction in the maximum quantum yield of photochemistry Fv/Fm and in the photosynthetic electron transport rate (ETR).